Comparison of two docking methods for peptide‐protein interactions. (26th February 2018) - Yu, Qiuying; Wang, Fangyu; Hu, Xiaofei; Xing, Guangxu; Deng, Ruiguang; Guo, Junqing; Cheng, Anchun; Wang, Jing; Hao, Junfang; Zhao, Dong; Teng, Man; Zhang, Gaiping
Abstract: BACKGROUND: The importance of peptides in regulatory interactions has caused peptide‐protein docking to attract the attention of many researchers. A variety of methods for molecular modeling of peptide‐protein docking, such as local search and global search, are currently used. RESULTS: The interactions of 11 peptides and CSFV E2 protein were evaluated by the GalaxyPepDock and FlexX/ SYBYL programs, respectively. The assessment scores of all the peptides were correlated with their KD values. The final results showed that a moderate correlation coefficient was represented between KD values and CScores of predicted models by FlexX/ SYBYL. CONCLUSION: Our results demonstrate that considering the flexibility of the peptide is better than searching for more potential binding sites on the target protein surface while performing peptide‐protein molecular docking. These data provide reasonable evidence for the molecular design of peptides and guidance for the functional assignment of target proteins. © 2018 Society of Chemical Industry